2020
DOI: 10.1002/anie.201913368
|View full text |Cite
|
Sign up to set email alerts
|

A Site‐Selective Doping Strategy of Carbon Anodes with Remarkable K‐Ion Storage Capacity

Abstract: The limited potassium‐ion intercalation capacity of graphite hampers development of potassium‐ion batteries (PIB). Edge‐nitrogen doping is an effective approach to enhance K‐ion storage in carbonaceous materials. One shortcoming is the lack of precise control over producing the edge‐nitrogen configuration. Here, a molecular‐scale copolymer pyrolysis strategy is used to precisely control edge‐nitrogen doping in carbonaceous materials. This process results in defect‐rich, edge‐nitrogen doped carbons (ENDC) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(121 citation statements)
references
References 50 publications
3
118
0
Order By: Relevance
“…As illustrated in Figure 4e and Table 1, the NPCF-800 with high doping level of the pyrrolic and pyridinic N represents one of the best performances of carbonaceous anodes used in PIBs. [18][19][20][21][22]24,26,27,[30][31][32][33][34]37,38,[45][46][47][48][49][50][51] Besides, such ultrafast potassium storage and excellent cycling stability have been seldom reported in PIBs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in Figure 4e and Table 1, the NPCF-800 with high doping level of the pyrrolic and pyridinic N represents one of the best performances of carbonaceous anodes used in PIBs. [18][19][20][21][22]24,26,27,[30][31][32][33][34]37,38,[45][46][47][48][49][50][51] Besides, such ultrafast potassium storage and excellent cycling stability have been seldom reported in PIBs.…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34] As demonstrated by calculation and experimental study, the pyrrolic N and pyridinic N were suggested to be effective in enhancing the reversible capacity of the electrode. [18,[35][36][37][38] However, developing N-doped carbon materials with high concentration of easily accessible active N species (pyrrolic and pyridinic N) for enhanced PIBs performance still remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Increased pyrolysis temperatures lead to higher I D / I G values (Figure b and Table S1). This is probably because at relatively lower temperature, ENPCS‐500 possesses a characteristic sp 2 ‐hybridized hexagon structure inherited from the pyridinic precursor; higher temperatures promote the decomposition and conversion to amorphous carbons with defect nanopores/nanovoids . From N 2 adsorption/desorption curves, ENPCSs exhibit predominately micropores with a narrow pore size around 0.5 nm and a less intense peak at 1.2 nm (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the N‐doped carbons require a higher carbonization temperature (≥600 °C), because further lower temperature leads to incomplete carbonization with reduced conductivity or heteroatom doping . This is likely due to the intrinsic properties of the precursors . The edge‐enriched N and high surface area will be beneficial for the interfacial adsorption for capacitive process.…”
Section: Resultsmentioning
confidence: 99%
“…In normal scenarios, there exist different configurations of N species within the carbon lattice, that is, pyridinic N, pyrrolic N, and graphitic N. Zhang and co-workers proposed a molecular-scale copolymer pyrolysis strategy to precisely control the edge-N (pyridinic N and pyrrolic N) doping in carbonaceous materials, resulting in edge-N doped carbons (ENDC) with a high edge-N ratio (87.6%). 63 In contrast to the low edge-N doped carbons (NDC900), ENDC harvested a higher reversible capacity of 423 mAh g −1 (Figure 2(A,B)). This illustrates that even if the same type of heteroatoms was doped, its different configurations exerted distinct effects on K + storage.…”
Section: Heteroatomic Dopingmentioning
confidence: 94%